EKONOMICZNE UWARUNKOWANIA FUNKCJONOWANIA GIEŁDY TOWAROWEJ NA RYNKU ROLNYM W POLSCE - Jerzak, Michał A. (Wydział Prawa i Administracji UAM, 2000)
Started in the early 90’s, systematic transformation in Poland brought a completely new economic reality to rural communities and agricultural sector. A direction of economic development taken at the time laid foundations for future creation of favourable conditions for the development of commodity exchanges as necessary instruments for proper functioning of market economy. In Poland, modem commodity exchanges have developed since 1990. During that period a model for a commodity exchange has evolved in adaptation to current economic conditions. Empirical studies were carried out, focusing on: — market orientation o f forms, — types of information needed and the sources of such information, — standardisation of goods, — perception of the role of commodity exchange. The studies confirm the opinions that Polish agricultural market was weak. Even though the market has a well-developed and, in many cases, modem technical infrastructure necessary for its proper functioning, it was proved that the market’s institutional and organisational dimensions as well as the educational barrier among market participants - do considerably slow down its growth. Under such circumstances, a commodity exchange - in addition to its statutory activities — needs to take part in a development of agricultural market institutions, adjusting thus the level of its own activity to their needs and requirements.
ECONOMICS ASPECTS OF THE OPERATION OF COMMODITY EXCHANGE ON THE AGRICULTURAL MARKET